NK cells in renal cell carcinoma and its implications for CAR-NK therapy - Li, Xinwei; Zhang, Yuanpeng; Ye, Yuzhong; Xiao, Wen; Liu, Lei; Zhang, Xiaoping (Frontiers in Cell and Developmental Biology, 2025)
Renal cell carcinoma (RCC) is a malignancy that makes up 3% of adult cancers and 20%–30% of patients were diagnosed with metastatic RCC in the beginning, while the median overall survival (OS) of metastatic RCC systemic therapy ranges from 16 months to 50 months. Immunotherapy, a novel therapy that relies on the specific binding of immune cells and tumor cells, may be a potential therapy for advanced renal cell carcinoma. While chimeric antigen receptor NK-cell (CAR-NK) therapy has been investigated in a variety of solid tumors, specific research on its application to RCC has also been reported by several teams. In this review, we introduced the cytotoxicity mechanisms of NK cells, summarized the connections between RCC and NK cells, and posted new insights into renal cell carcinoma CAR-NK therapy. To date, most researches focusing on renal cell carcinoma and NK cells only claimed the mechanisms of NK cell cytotoxicity and NK cell immune suppression and even immune escape, yet the molecules involved could also be interesting targets for renal cell carcinoma CAR-NK therapy.